Uma morte em família : martírio e autoridade nos 100 dias de cobertura do caso Tim Lopes em O Globo - Castilho, Marcio de Souza (2007)
This work intends to analyze the coverage of Tim Lopes´ case at O Globo, trying to understand the reason why the journalist transformed the murder of Tim Lopes into an event of enormous repercussion. We start pre-supposing that, despite the speech defending democracy and against the criminality, the intense coverage was associated directly to the question of the journalistic authority. Thus, the episode worked to give strength to the role of social investigative reporters and validate the role of journalists as producers of the truth. The objective of this dissertation is identify the imbrications of the narrative with this group validation strategies. A journal starts to construct the biography of Tim Lopes and reinvidicates the role of public memory of the case. It also adopts series with strategies of noticebility , anchored on a suppose succinct goal, so the speech can keep it self coherent with the interpretation given by journalist to the episode. Narrative resources are still used by the ones who appeal to the public sensation, thru then presentation if news with high dramatic appeal, on witch there are remarkable dualities. Starting from the construction of the psychological profile of the central character on the intrigue, the subjects reinforce the generosity of the victim and the importance of the investigate feature opposing the horrible character of the drug-dealer Elias Maluco. At this operation readers have been searched to join in reinforcing the authority of the journal before the facts making only one memorable version about the murder.